Integrating Artificial Intelligence in English Language Learning: A Systematic Literature Review - Prayogo, Lego; Agustin, Rizka Kamalia; Puspita, Bella (JEdu: Journal of English Education, 2025)
The rapid development of Artificial Intelligence (AI) has had a significant impact on education, particularly in English language learning. AI offers more adaptive, personalized, and interactive learning approaches that can be tailored to individual learner needs. This study aims to systematically review empirical literature on AI integration in English language learning published between 2021 and 2025. Using the Systematic Literature Review (SLR) method and following PRISMA guidelines, a total of 23 articles from Crossref and Google Scholar were analyzed based on educational level, type of technology used, and learning outcomes. The findings reveal that AI is most widely applied at the secondary and university levels, with chatbot technology being the most dominant. The main impact of AI integration includes improved language skills (speaking, writing, reading, listening), enhanced learning motivation, automated feedback, and flexible learning. The study concludes that AI contributes positively to the effectiveness of English language learning, although challenges such as infrastructure readiness and teachers' digital competence still need to be addressed for optimal implementation.